Death - Richardson, Henry Handel, 1870-1946 ([London : Printed for private circulation], 1911)
Richardson's second separately issued work of a short story. It has been reset by a different printer with Richardson's revision of the text. It is not an offprint from the English review. The title was later changed to Mary Christina.
Cover title.
Also available online
Papers and correspondence of Henry Handel Richardson 1852-1983. Series 5.
Keywords: Australian